2013
DOI: 10.1371/journal.pone.0072592
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Expression, Cellular Localization, and Function of Three Inhibitors of Apoptosis (IAPs) from Litopenaeus vannamei during WSSV Infection and in Regulation of Antimicrobial Peptide Genes (AMPs)

Abstract: Inhibitors of apoptosis (IAPs) play important roles in apoptosis and NF-κB activation. In this study, we cloned and characterized three IAPs (LvIAP1-3) from the Pacific white shrimp, Litopenaeusvannamei . LvIAP1-3 proteins shared signature domains and exhibited significant similarities with other IAP family proteins. The tissue distributions of LvIAP1-3 were studied. The expression of LvIAP1-3 was induced in the muscle after white spot syndrome virus (WSSV) infection. LvIAP1 expression in the gill, hemocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 62 publications
1
14
0
2
Order By: Relevance
“…vannamei were shown to be up-regulated post infection suggesting protective roles of IAPs in shrimp defense against WSSV infection [34]. In the present study, by microarray analysis we observed IAP to be down-regulated at initial stages (6 and 24 h) of WSSV infection and subsequently up-regulated from 48 hpi.…”
Section: Discussionsupporting
confidence: 61%
“…vannamei were shown to be up-regulated post infection suggesting protective roles of IAPs in shrimp defense against WSSV infection [34]. In the present study, by microarray analysis we observed IAP to be down-regulated at initial stages (6 and 24 h) of WSSV infection and subsequently up-regulated from 48 hpi.…”
Section: Discussionsupporting
confidence: 61%
“…24 Similarly, characterization of the three IAP genes in the Pacific white shrimp, Litopenaeus vannamei revealed their differential contributions to responding to white spot syndrome virus (WSSV) infection and expression of antimicrobial peptides. 25 Our results revealed that LmIAP1 also regulates antimicrobial peptide expression in response to fungal infection, with RNAi-mediated knockdown of LmIAP1 resulting in decreased transcription of antimicrobial peptides in the locust fat body after fungal infection, suggesting that LmIAP1 could be involve in humoral immunity to fungal infection. wileyonlinelibrary.com/journal/ps Apart from the fat body, hemocytes are other crucial insect immune-mediating tissues that function in cellular immunity.…”
Section: Discussionmentioning
confidence: 62%
“…RNAi‐mediated knockdown of this gene resulted in a reduced ability of the insect to induce expression of antimicrobial peptides in response to bacterial pathogens, and increased the susceptibility of the insect to infection by Gram‐negative bacteria . Similarly, characterization of the three IAP genes in the Pacific white shrimp, Litopenaeus vannamei revealed their differential contributions to responding to white spot syndrome virus (WSSV) infection and expression of antimicrobial peptides . Our results revealed that LmIAP1 also regulates antimicrobial peptide expression in response to fungal infection, with RNAi‐mediated knockdown of LmIAP1 resulting in decreased transcription of antimicrobial peptides in the locust fat body after fungal infection, suggesting that LmIAP1 could be involve in humoral immunity to fungal infection.…”
Section: Discussionmentioning
confidence: 71%
“…27 IAP proteinlerinde BIR domainine ek olarak Nterminal kaspaz organize edici bölge [caspase recruitment domain (CARD)] ve TRAF1 ile TRAF2'nin düzenlenmesine yardımcı ve TNF-αapoptotik sinyalizasyonunu inhibe eden ubikitin ligaz aktivitesinden sorumlu RING domaini de yer almaktadır. 28 Bugüne kadar insanlarda sekiz farklı IAP proteini tanımlanmıştır. Bu proteinler; nöronal apoptoz inhibe edici protein, hücresel apoptoz proteini inhibitörü-1 (c-IAP1), hücresel apoptoz proteini inhibitörü -2 (c-IAP2), apoptoz proteninin X'e bağlı inhibitörü (XIAP), baculovirus IAP tekrar (BIR) domaini-6 (Apollon), Livin, ILP-2 ve BIR domaini-5 (Survivin) olarak belirlenmiştir.…”
Section: Bcl-2 Proteinleriunclassified